2017
DOI: 10.1016/j.applthermaleng.2016.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Development and calibration of a model for the dynamic simulation of fans with induction motors

Abstract: In this paper a model for the dynamic simulation of fans used in mechanical air supply systems is described. Thanks to this model, the behavior of fans subject to control by variable frequency drives (VFD) can be predicted, which includes power absorbed by the fan and expected ventilation rates. Hence, it can help design energy control systems for buildings. The proposed model was based on the Modelica language and was developed from the dynamic phasor domain representation, because this representation is a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Mechanical power, generated by the electric motor of each fan is partly converted to hydraulic work by the cooling tower fan, based on the hydraulic efficiency [25]. In [8], the first two fan affinity laws are shown that relates flow through the fan (F f ), pressure head created (p f ), and power (P f ) to fan speed (n), from one steady-state operating point (point 0) to another one (point 1) as follows:…”
Section: Fan Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical power, generated by the electric motor of each fan is partly converted to hydraulic work by the cooling tower fan, based on the hydraulic efficiency [25]. In [8], the first two fan affinity laws are shown that relates flow through the fan (F f ), pressure head created (p f ), and power (P f ) to fan speed (n), from one steady-state operating point (point 0) to another one (point 1) as follows:…”
Section: Fan Modellingmentioning
confidence: 99%
“…The valves are modelled as per (25) in this paper [32]. The actual volume flow (F/ρ w ) is proportional through the valve coefficient C vCV to the product of the valve characteristic f (.…”
Section: Control Valve Modellingmentioning
confidence: 99%
“…Many fans, as the one analyzed in this study, are driven by induction motors. Likewise, in power plants, fans driven by induction motors are also used for air supply systems of buildings and are responsible for significant power consumption [29]. A detailed CFD analysis of the fan electrical drive was presented by Ding et al [30].…”
Section: Introductionmentioning
confidence: 99%
“…In one case in which a French railway station building was modeled and its thermal and electrical loads estimated, the validation deviations were below 10% [16]. The same tool was suitable for accurately modeling single components of building equipment, such as a slinky-coil geothermal heat pump system [17] and mechanical air supply systems in subway stations [18]. Once the parameters are calibrated through comparison with real measured performance, the model can be used as the basis for the simulation of system regulation and control alternatives [19].…”
Section: Introductionmentioning
confidence: 99%